Health-related quality of life in narcolepsy: A systematic review and meta-analysis - Broderick, Julie; Mockler, David (My University, 2021)
To date, there has been no systematic analysis of the literature regarding health-related quality of life in narcolepsy. This systematic review aimed to examine the impact of narcolepsy on health-related quality of life, measured through standardised health-related quality of life questionnaires such as the Short Form 36 and Functional Outcome of Sleep Questionnaire. The following databases: Medline, Embase, Cinahl, and Web of Science were searched for studies that investigated health-related quality of life in adults with narcolepsy. Studies were reviewed independently by two reviewers, and a random-effects meta-analysis was performed. A total of 30 studies were eligible for inclusion in the review. Additionally, meta-analyses were conducted for the Short Form 36 and the EQ5D. The Short Form 36 meta-analysis identified that the pooled mean scores for the Physical Component Summary (45.91) were less affected than the Mental Component Summary (42.98). People with narcolepsy experience substantially lower health-related quality of life when compared with the general population norms of the USA, UK, France and Norway, as well as compared with people with chronic diseases such as multiple sclerosis, diabetes, hypertension and epilepsy. Further research is warranted to identify the longitudinal effects of narcolepsy on health-related quality of life, and to develop a narcolepsy-specific health-related quality of life tool.
PUBLISHED
Keywords: Diabetes mellitus; Epilepsy; Nervous system disorders; Diabetes mellitus; Type 2; Hypertension and diabetes; Adult; Chronic disease; Multiple sclerosis; Narcolepsy; Norway; Quality of life; Correlation studies; Health-related quality of life; Mental Health/Psychosocial disability; Physical disability